Influence of catalyst support characteristics and functionalization on the catalytic activity of Pt-Ru for PEM fuel cells - Calderon, J. C. (2012)
Pt-Ru electrocatalysts supported on carbon xerogels and ordered mesoporous carbons were synthesized by reduction with formate ions (SFM method). Chemical and heat treatments were applied to modified the surface chemistry of original carbon supports. Physical characterization of the catalysts was performed using X-ray dispersive energy (EDX) and X-ray diffraction (XRD) techniques, while the electrochemical activity towards methanol oxidation was studied by cyclic voltammetry (CV). Pt-Ru catalysts with nominal metal content (20 wt.%) and atomic ratios (Pt:Ru 1:1) were successfully synthesized on the different supports. Higher methanol oxidation current densities were obtained for those supports with a higher content of surface oxygen groups. Gas diffusion electrode and membrane-electrode-assembly preparation allowed an in-house built of a direct methanol fuel monocell for the evaluation of the catalysts performance. Polarization curves were measured confirming the results obtained in a three electrodes electrochemical cell by CV. Normalized power curves per weight of Pt are discussed in terms of the significant impact on noble metal loading and attained cell maximum power, in comparison with results obtained with a commercial catalyst